IDENTIFIKASI DAN UJI AKTIVITAS SENYAWA TANIN DARI EKSTRAK DAUN TREMBESI (Samanea saman (Jacq.) Merr) SEBAGAI ANTIBAKTERI Escherichia coli (E. coli) - Putu Puspita Sari; Wiwik Susanah Rita; Ni Made Puspawati (Jurnal Kimia (Journal of Chemistry), 2015)
Isolation and identification of tannin compounds from trembesi leaves (Samanea saman (Jacq.) Merr) and its anti-bacterial activity test against Escherichia coli (E. coli) have been done in this research based on the utilization of trembesi leaves to treat diarrhea. Extraction was done by maceration and partition, separation by preparative TLC. The anti-bacterial activity was tested using wells that diffusion method, and the identification of the compounds was done with UV-vis spectrophotometer and FTIR. Maceration with ethanol produced 36.80 g crude ethanol extract. Phytochemical test showed that acetone and water fractions gave positive result for hydrolyzed tannin compounds but acetone fraction revealed more concentrated than water fraction. Anti-bacterial test result showed that the acetone fraction was active towards E.coli with medium activity. Separation of the eluent n-butanol: acetic acid: water (4:1:5) (BAA) gave six isolates but only two isolates (isolate 2 with Rf 0.61, and isolates 3 with Rf.0.65) gave positive results for tannin. These two isolates were relatively pure on TLC purity test and showed weaker anti-bacterial activity compared to the acetone fractions. Identification using UV-Vis spectrophotometer showed that isolates 2 and 3 gave two similar peaks with maximum absorbance at 346.50 nm and 347.00 nm respectively due to n?*and ??* electron transitions, which indicated the presence of C=O  and C=C chromophores.  Infrared spectra of isolates 2 and 3 revealed peaks that correspond to characteristic functional groups of tannin including –O-H, C-H aliphatic, C=O esther, C=C aromatic, C-O-H, and C-O-C ether.